Pendampingan Literasi Digital Guru Paud Melalui Pemanfaatan Smartphone Untuk Produksi Video Pembelajaran Kontekstual - Lilianti Lilianti; Rusdin Rusdin; Sunarmin Sunarmin; Sinarlin Sinarlin; Samsudin Samsudin; Suliani Suliani; Iin Nurnaningsih; Asliatin Asliatin; Deden Plasna; Arzak Arzak (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service program aims to improve the digital literacy of Pelita Ibu Kendari PAUD teachers, specifically in producing contextual learning videos based on the Canva application through the use of smartphones. The implementation method uses a participatory learning-by-doing approach, implemented on January 2, 2026. The results of the activity showed significant changes; before mentoring, only 2 teachers (33.3%) were able to make simple videos, while after the program, all teachers (100%) succeeded in producing at least 2 local context-based learning videos with a duration of 3–5 minutes that integrate the child's environment and the teacher's personal figure. In conclusion, structured mentoring based on portable devices has proven effective as a model for strengthening PAUD teachers' digital literacy that is applicable and sustainable.